Taxonomic notes on Vaccinium glaucophyllum (Ericaceae): supplementary description of floral morphology and sectional reassignment (Ericaceae) - Ye, Xue-He; Tong, Yi-Hua; Yang, Cheng-Hua; Dai, Xiao-Yong; Xia, Nian-He; Zhou, Hou-Gao (Phytotaxa, 2021)
The floral morphological description of Vaccinium glaucophyllum is supplemented based on newly collected flowering material. This species is reassigned to V. section Calcicolus based on its evergreen habit, dimorphic perennating buds, racemose inflorescences with large caducous bracts and pseudo-10-loculed ovary with 2–5 seeds. The information on its type, distribution and conservation status together with color photos is also provided.